Toner

By forming a hierarchical structure of silicone polymer and metal compounds on the surface of toner particles, the problem of toner charge instability caused by foreign matter mixing is solved, and a more stable image output and a longer toner life are achieved.

JP2025043952APending Publication Date: 2025-04-01CANON KK
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023151573
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-19
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

In a clean system-free system, foreign matter such as limestone and deformed toner can be mixed into the development equipment, causing the toner charge to be unstable and increasing the risk of image damage such as fog, ghosts and white strips.

Method used

Toner particles containing silicone polymer and metal compounds are used to improve the relative dielectric constant and charge storage capacity of the toner by controlling the distribution and domain size of the metal compounds.

Benefits of technology

Even in the presence of foreign matter, the toner can maintain good charge stability, reduce the risk of image damage, and extend the service life of the toner.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025043952000001
    Figure 2025043952000001
  • Figure 2025043952000002
    Figure 2025043952000002
  • Figure 2025043952000003
    Figure 2025043952000003
Patent Text Reader

Abstract

To provide a toner that has excellent electrostatic properties, and reduces the occurrence of adverse effects on an image, such as fogging, ghost, and white streaks caused by fusion of the toner on a blade, even when a foreign substance, such as talc is mixed in a developing device in a cartridge or when a large amount of deformed toner is present in the developing device.SOLUTION: A toner contains toner particles. The toner particles each have a toner base particle containing a binder resin, and an organic silicon polymer complex present on the surface of the toner base particle. The organic silicon polymer complex contains (i) a condensate of an organic silicon compound, and (ii) a metal compound containing at least one metal atom selected from the group consisting of aluminum, zirconium, and titanium. When the toner is analyzed, predetermined relational expressions for domains of constituents and the metal compound are satisfied.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to toners used in copying machines and printers using electrophotography or electrostatic recording methods. [Background technology]

[0002] In recent years, printers and copiers are widely required to be compact while providing high image quality and long life. In order to make printers more compact, it is mainly effective to make the process cartridge (hereinafter also referred to as cartridge) more compact. Cartridges are generally equipped with a cleaning container, but in recent years, cleanerless systems that do not have a cleaning container have been proposed. In many printers, the toner (residual toner after transfer) remaining on the electrostatic latent image carrier (hereinafter also referred to as photoconductor) in the transfer process is scraped off by a cleaning blade or the like and collected in a cleaning container as waste toner. On the other hand, cleanerless systems do not have a cleaning blade or cleaning container, so the process cartridge can be made smaller, and the residual toner after transfer is collected in the developing device and contributes to development again, leading to a longer life.

[0003] However, there are some unique problems with cleanerless systems. One of them is that fillers and additives such as paper, which is the media, adhere to the surface of the photoconductor and are collected as foreign matter in the developing device of the cartridge. If these foreign matters get into the developing device, the toner will not be properly charged, and image problems will likely occur. In particular, in a developing system that negatively charges the toner, if paper containing talc is used as the media, the charge of the toner will decrease if the talc is collected in the developing device. This is because talc has a characteristic that it is easily charged negatively, and when it rubs against the toner, the toner tends to be relatively charged positively. As a result, the charge distribution becomes broad, and image problems such as fogging and image problems such as ghosting due to the slow rise in charge are likely to occur. Against this background, there is a demand for a toner that can ensure stable charging even if talc gets into the developing device.

[0004] In addition, in a cleanerless system, the residual toner after transfer is developed once and then collected in the developing device again, which increases the number of times it is rubbed, making it more likely to become deformed due to chipping and cracking. Deformed toner has a lower chargeability and is therefore less likely to be developed, and is more likely to remain in the developing device. As the amount of deformed toner increases, the fluidity of the toner decreases, and the toner remains between the regulating blade and the developing roller, causing fusion to the regulating blade and making it more likely to cause image defects such as white streaks. In order to prevent the increase in deformed toner in the developing device, it is important to charge and develop the deformed toner and discharge it from the developing device. For this purpose, it is desirable to be able to charge even the deformed toner.

[0005] In order to stably charge a toner, Patent Document 1 proposes a method of incorporating an organosilicon polymer composite and a highly conductive metal compound in the shell portion on the outermost surface of the toner. By configuring the shell in this way, it is possible to improve triboelectric charging properties, suppress leakage, and maintain excellent charge rise properties and stable charging properties. Similarly, Patent Document 2 proposes a method in which an organosilicon polymer composite and a metal compound are contained in the shell portion, the location of the metal compound is controlled, and then a charge is imparted to the toner by utilizing the potential difference generated between the developing roller and the regulating blade. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Patent Publication No. 2021-21789 [Patent Document 2] Patent Publication No. 2021-21790 Summary of the Invention [Problem to be solved by the invention]

[0007] However, the inventors' research revealed that in the methods described in Patent Documents 1 and 2, since the metal compound is exposed in the shell, the charge leaks and the charging is insufficient in an environment where charging control is stricter. In particular, when talc is mixed into the developing device or when there is a large amount of deformed toner, the inventors found that there is a problem that sufficient charging property cannot be obtained and image defects are likely to occur.

[0008] One aspect of the present disclosure is to provide a toner that has excellent charging properties and is less likely to cause image defects such as fog, ghosting, and white streaks due to blade fusion, even when foreign matter such as talc is mixed into the developing device of the cartridge or when a large amount of irregularly shaped toner is present. [Means for solving the problem]

[0009] According to one aspect of the present disclosure, A toner comprising toner particles, The toner particles are toner base particles containing a binder resin; an organosilicon polymer composite present on the surface of the toner base particle; The organosilicon polymer composite comprises: (i) condensation products of organosilicon compounds, and (ii) a metal compound containing at least one metal atom selected from the group consisting of aluminum, zirconium, and titanium; Contains ME is a ratio of the number of the metal atoms to the sum of the numbers of carbon atoms, oxygen atoms, silicon atoms, and the metal atoms, which is obtained by X-ray photoelectron spectroscopy of the toner, In an EDS mapping image of constituent elements of a cross section of the toner, which is obtained by analyzing the cross section of the toner observed with a scanning transmission electron microscope with an energy dispersive X-ray spectrometer, a ratio of the number of the metal atoms to the total number of the silicon atoms and the metal atoms in a region outside the contour of the toner base particle is defined as MX, In the EDS mapping image, domains of the metal compound are present, and when the domain diameter is 10 nm or more, the number average diameter of the domains of the metal compound is defined as MN, The ME is 1.5 x 10 -2 is as follows: The MX is 1.00 x 10 -2 Above 1.00 x 10 -1 is as follows: The MN is 15 nm or more and 80 nm or less. A toner is provided, which comprises: Effect of the Invention

[0010] According to at least one aspect of the present disclosure, it is possible to provide a toner that has excellent charging properties and is less likely to cause image defects such as fog, ghosting, and white streaks due to blade fusion, even when foreign matter such as talc or irregularly shaped toner is present in the developing device of the cartridge. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] In the present disclosure, the description of a numerical range such as "XX or more and YY or less" or "XX to YY" means a numerical range including the lower and upper limits, which are the endpoints, unless otherwise specified. When a numerical range is described in stages, the upper and lower limits of each numerical range can be arbitrarily combined. In addition, in the present disclosure, a description such as "at least one selected from the group consisting of XX, YY, and ZZ" means any of XX, YY, ZZ, a combination of XX and YY, a combination of XX and ZZ, a combination of YY and ZZ, or a combination of XX, YY, and ZZ.

[0012] The present disclosure will be described in detail below. The present inventors have conducted research into toner that exhibits excellent charging properties even when talc is mixed into the developing device or when the amount of deformed toner increases, and have found that the following toner is effective. That is, a toner containing toner particles, The toner particles are toner base particles containing a binder resin; an organosilicon polymer composite present on the surface of the toner base particle; The organosilicon polymer composite comprises: (i) condensation products of organosilicon compounds, and (ii) a metal compound containing at least one metal atom selected from the group consisting of aluminum, zirconium, and titanium; Contains ME is a ratio of the number of the metal atoms to the sum of the numbers of carbon atoms, oxygen atoms, silicon atoms, and the metal atoms, which is obtained by X-ray photoelectron spectroscopy of the toner, In an EDS mapping image of constituent elements of a cross section of the toner, which is obtained by analyzing the cross section of the toner observed with a scanning transmission electron microscope with an energy dispersive X-ray spectrometer, a ratio of the number of the metal atoms to the total number of the silicon atoms and the metal atoms in a region outside the contour of the toner base particle is defined as MX, In the EDS mapping image, domains of the metal compound are present, and when the domain diameter is 10 nm or more, the number average diameter of the domains of the metal compound is defined as MN, The ME is 1.5 x 10 -2 is as follows: The MX is 1.00 x 10 -2 Above 1.00 x 10 -1 is as follows: The MN is 15 nm or more and 80 nm or less. The toner is characterized in that:

[0013] The present inventors consider the reason why the toner having such a composition exhibits the above-mentioned effects as follows. First, the inventors of the present invention paid attention to the toner charging process when examining the control of the chargeability of the toner. The current toner charging process mainly uses frictional charging, but if foreign matter such as talc that is easily negatively charged is mixed into the developing device, friction between the talc and the toner also occurs when the regulating member and the toner rub against each other, and the toner that should be negatively charged is likely to be positively charged. As a result, the distribution of the charge amount is not sharp, and toner with a high charge amount and toner with a low charge amount may occur. Furthermore, since frictional charging is greatly affected by the fluidity of the toner, if the toner is rubbed many times and chipped or cracked, and the fluidity is reduced, the charge amount is likely to decrease. Thus, the charging process by frictional charging is insufficient in terms of precise charge control. Therefore, considering that precise charge control is required in a harsher environment, a fundamentally different charging process is required.

[0014] Therefore, the present inventors have investigated injection charging as a charging process different from friction charging. Injection charging is a charging process in which a charge is imparted to a toner by a potential difference generated between a regulating member and a developing roller in a developing device. If it is possible to give the toner injection charging property, which is charged by a potential difference, in addition to the conventional friction charging property, the charging of the toner can be controlled more precisely.

[0015] Incidentally, it is known that when toner is placed in an electric field, the charge amount changes according to the potential difference, as shown in the following formula (1). Q = C V (1) (In formula (1), Q represents the charge amount of the toner, C represents the electrostatic capacitance of the toner, and V represents the potential difference.) In this case, the proportionality constant C is the electrostatic capacitance of the toner and can be expressed by the following equation (2). C=ε r C0 (2) (In formula (2), ε r is the relative dielectric constant of the toner, and C0 is the capacitance of a vacuum. That is, the relative dielectric constant ε r The larger the potential difference, the larger the amount of charge that can be applied.

[0016] As described above, in the injection charging process, the relative dielectric constant ε r By controlling the relative dielectric constant ε r By increasing the toner density, a large amount of charge can be imparted to the toner by the potential difference generated between the regulating member and the developing roller, so that even if foreign matter such as talc is present, the toner can be sufficiently charged. In addition, although the amount of triboelectric charge decreases with the decrease in fluidity of toner that has become deformed due to cracking or chipping, it is possible to impart a charge to such toner. As a result, it is possible to develop the deformed toner as well, and prevent the concentration of the deformed toner from increasing in the developing container.

[0017] The present inventors have discovered that the toner has a composition comprising toner particles, the toner particles having toner base particles containing a binder resin and an organosilicon polymer composite on the surface of the toner base particles, the organosilicon polymer composite being (i) condensation products of organosilicon compounds, and (ii) By incorporating a metal compound containing at least one metal atom selected from the group consisting of aluminum, zirconium, and titanium, the relative dielectric constant ε of the toner is reduced. r The reason for this is thought to be as follows.

[0018] Relative permittivity ε r In order to increase the relative dielectric constant ε, it is effective to selectively use toner materials having different volume resistivities. r is an index of the ease of polarization of an insulator. When a high-resistance material and a low-resistance material coexist in an electric field, a charge bias occurs first in the low-resistance material, which induces and increases the polarization of the high-resistance material. In this way, by having an organosilicon polymer composite, which has a lower resistance than the binder resin, present on the surface of a toner base particle containing a binder resin, which is a high-resistance material, polarization of the binder resin is induced in an electric field, resulting in a high dielectric constant ε rAs an example of a resin that is preferably used as a binder resin for toner, there is a styrene resin, and the volume resistivity of polystyrene is about 1.0×10 14 On the other hand, organic silicon compounds are classified as insulators. However, its resistance is lower than that of the binder resin. For example, the volume resistivity of silicone rubber is about 1.0×10 12 ~1.0×10 13 In this way, by selectively using materials with different resistivities, the relative dielectric constant ε r It becomes possible to control.

[0019] Furthermore, the organosilicon polymer composite according to one embodiment of the present disclosure contains (i) a condensate of an organosilicon compound, and (ii) a metal compound containing at least one metal atom selected from the group consisting of aluminum, zirconium, and titanium (hereinafter also referred to as a specific metal atom). These metal atoms have a valence of three or more, and are characterized by having a large number of free electrons. When a metal compound containing such a metal atom is placed in an electric field, the free electrons immediately move, causing a large charge imbalance within the metal compound. By allowing such a metal compound to coexist with a condensate of an organosilicon compound, polarization of the condensate of the organosilicon compound is induced in an electric field, resulting in a dielectric constant ε r can be further increased.

[0020] Thus, the relative dielectric constant ε r A toner with a large dielectric constant ε can store a large amount of charge on the toner surface in an electric field. For example, the polyvalent acid metal salt used in Patent Documents 1 and 2 has excellent electrical conductivity, and when it is contained in an organosilicon polymer composite together with a condensate of an organosilicon compound, it has a dielectric constant ε r can be made larger.

[0021] On the other hand, if a metal compound is exposed on the surface of the toner, the free electrons of the metal compound may leak to the developing roller, or the charge stored on the toner surface due to the potential difference may leak through the metal compound, resulting in a decrease in the amount of charge. When a highly hydrophobic organosilicon condensate is used together with a less hydrophobic polyvalent acid metal salt as used in Patent Documents 1 and 2, the polyvalent acid metal salt is likely to be exposed on the surface of the organosilicon polymer composite or the surface of the toner base particle. In such a case, in a more severe charging environment, the charge leaks from the toner, and image defects due to insufficient charging are likely to occur. Therefore, when a highly conductive metal compound is used, it is necessary to suppress the exposure of the metal atoms.

[0022] Therefore, when the ratio of the number of specific metal atoms to the sum of the numbers of carbon atoms, oxygen atoms, silicon atoms, and specific metal atoms (at least one metal atom selected from aluminum, zirconium, and titanium) obtained by X-ray electron spectroscopy analysis (ESCA) of the toner is defined as ME, the ratio of the number of specific metal atoms to the sum of the numbers of carbon atoms, oxygen atoms, silicon atoms, and specific metal atoms (at least one metal atom selected from aluminum, zirconium, and titanium) obtained by X-ray electron spectroscopy analysis (ESCA) of the toner is 1.5×10 -2 It is important that: In addition, the cross section of the toner observed with a scanning transmission electron microscope (STEM) is analyzed with an energy dispersive X-ray spectrometer (EDS) to obtain an EDS mapping image of the constituent elements of the cross section of the toner. In the EDS mapping image, when the ratio of the number of specific metal atoms to the sum of the numbers of silicon atoms and specific metal atoms in the region outside the contour of the toner mother particle is MX (number of specific metal atoms / sum of the numbers of silicon atoms and specific metal atoms), MX is 1.00×10 -2 Above 1.00 x 10 -1 It is important that:

[0023] ME indicates the ratio of specific metal atoms present on the surface or near the surface of the toner. The lower the ME value, the fewer the specific metal atoms present on the surface or near the surface. -2 If the capacitance is less than 1.5×10, the charge leakage can be suppressed to a high degree. -2 If the charge leakage exceeds this value, it becomes difficult to control the charge leakage, and image defects due to insufficient charging are likely to occur. ME is preferably 1.2 x 10 -3 ~1.2×10 -2 and more preferably 2.5×10 -3~1.0×10 -2 It is. In order to control ME and MX within the above numerical ranges, it is effective to surface treat the metal compound particles with an organosilicon compound, as will be described in detail later.

[0024] The amount of metal atoms contained in the organosilicon polymer composite is also important. In the EDS mapping image of the cross section of the toner, the "region outside the outline of the toner base particle" refers to the organosilicon polymer composite present on the surface of the toner base particle. MX represents the number of detectable specific metal atoms inside the organosilicon polymer composite, and the value of MX is 1.00×10 -2 If the toner has a relative dielectric constant ε r can be sufficiently controlled, and a sufficient amount of charge can be obtained. On the other hand, if the MX value is 1.00 × 10 -1 If the metal atom content exceeds this value, it means that the amount of metal atoms contained in the organosilicon polymer complex is large. As a result, the metal atoms exposed on the toner surface will increase, or even if not exposed, the metal atoms present near the surface within the organosilicon polymer complex will increase. If the number of metal atoms present near the surface increases, insulation breakdown will occur, making it easier for charges to leak, making it difficult to precisely control the chargeability. MX is 2.00 x 10 -2 ~8.00×10 -2 is preferred, 2.50×10 -2 ~7.60×10 -2 is more preferred.

[0025] Furthermore, it is also important to control the domain diameter of the metal compound in the organosilicon polymer composite. In the toner according to one embodiment of the present disclosure, when the domain of the metal compound exists in the EDS mapping image and the domain diameter is 10 nm or more, the number average diameter of the domain of the metal compound is MN, and the MN is 15 nm or more. Since the amount of free electrons of the metal compound is proportional to the size of the metal compound, when MN is 15 nm or more, the charge bias becomes large when the free electrons move in the metal compound under an electric field. Therefore, the polarization of the condensation product of the organosilicon compound can be effectively performed. On the other hand, if MN exceeds 80 nm, even if the metal compound is encapsulated in the organosilicon polymer composite, it is likely to be detached by rubbing in the developing container, and the chargeability changes during use. As a result, image defects are likely to occur. A more preferred range of MN is 20 nm to 50 nm, and an even more preferred range is 30 nm to 35 nm. The M N can be controlled by the particle size of the metal compound contained in the organosilicon polymer composite.

[0026] The ME and MX values ​​satisfying the above ranges mean that a certain amount of metal atoms are present inside the organosilicon polymer composite, but only a small amount of metal atoms are present on the surface or near the surface of the toner.Furthermore, the MN value satisfying the above ranges means that a part of the metal compound is enveloped as a domain in the condensation product of the organosilicon compound.By configuring the toner in this way, the chargeability of the toner can be suitably controlled and leakage can be suppressed.

[0027] In the toner according to the present disclosure, the coverage of the toner base particles with the organosilicon polymer composite is preferably 35 area % or more and 70 area % or less. As mentioned above, when an organosilicon polymer composite having a lower resistance than the binder resin is placed on the surface of a toner base particle containing an insulating binder resin, polarization of the binder resin is induced in an electric field, resulting in a high relative dielectric constant ε rcan be increased. As a result, when the toner is placed in an electric field, a large amount of charge can be stored on the surface. If the coverage of the toner base particles with the organosilicon polymer composite is 35 area % or more, polarization of the binder resin is easily induced, which is preferable. On the other hand, if the coverage is 70 area % or less, the toner is less likely to charge up, making it easier to precisely control the charge. The coverage is more preferably 40 area % to 65 area %, and particularly preferably 45 area % to 60 area %.

[0028] The coverage of the toner base particles can be adjusted by the amount of the organosilicon compound and the pH. By increasing the amount of the organosilicon compound, the coverage can be increased. On the other hand, by decreasing the amount of the organosilicon compound, the coverage can be decreased. In addition, by increasing the pH, the condensation of the organosilicon compound proceeds more easily, and the condensation between the organosilicon compounds proceeds not only on the surface of the toner base particles but also in water. As a result, the coverage of the organosilicon polymer composite on the surface of the toner base particles can be reduced. The content of the organosilicon polymer complex is preferably 3 to 10 parts by weight per 100.0 parts by weight of the toner base particles.

[0029] The toner according to the present disclosure contains a metal compound containing at least one metal atom selected from the group consisting of aluminum, zirconium, and titanium, with titanium being particularly preferred among these metal atoms. The content of the metal compound is preferably 0.05 part by mass to 1.0 part by mass with respect to 100.0 parts by mass of the toner base particles.

[0030] The volume resistivity of each metal (at 20°C) is 2.8×10 for aluminum. -8 (Ω·m), zirconium 40.6×10 -8 (Ω·m), titanium 53.3×10 -8 (Ω· m). Metal compounds containing these metal atoms are present within the organosilicon polymer composite. However, if the metal compound is located near the surface of the organosilicon polymer composite, if the volume resistivity is too low, insulation breakdown will occur in the electric field and the charge will easily leak. Of these, titanium has the highest volume resistivity, and is preferably used because it allows the chargeability to be controlled without being affected much by the location of the metal compound in the organosilicon polymer composite.

[0031] Specific examples of metal compounds containing titanium atoms include titanium oxides such as titanium dioxide, titanic acid compounds such as potassium titanate, calcium titanate, strontium titanate, and barium titanate, and reaction products of titanium and polyvalent acids. Specific examples of polyvalent acids include inorganic acids such as phosphoric acid (trivalent), carbonic acid (divalent), and sulfuric acid (divalent); and organic acids such as dicarboxylic acid (divalent) and tricarboxylic acid (trivalent). Specific examples of organic acids include dicarboxylic acids such as oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, fumaric acid, maleic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, phthalic acid, isophthalic acid, and terephthalic acid; and tricarboxylic acids such as citric acid, aconitic acid, and trimellitic anhydride. Examples of reaction products of titanium and polyvalent acids include titanium phosphate compounds, titanium sulfate compounds, titanium carbonate compounds, and titanium oxalate compounds. Among these, titanium dioxide and the reaction product of titanium and polyacid are preferred because they have a high affinity with the condensation product of the organosilicon compound. As will be described later, when forming the organosilicon polymer composite on the surface of the toner base particle, there is a method in which the organosilicon compound is hydrolyzed and then put into the aqueous medium in which the toner base particle is dispersed. Titanium dioxide has high hydrophilicity, and the reaction product of titanium and polyacid also has high hydrophilicity because the polyacid is ionized in water. These metal compounds have a high affinity with the hydrolyzate of the organosilicon compound, and the surface of the metal compound can be treated with the condensation product of the organosilicon compound. As a result, the metal compound is easily present in the organosilicon polymer composite without being exposed. That is, the metal compound is preferably at least one metal compound selected from the group consisting of titanium dioxide and a reaction product of titanium and a polyvalent acid. Titanium dioxide is more preferably selected because it has a large number of free electrons and tends to have a large charge imbalance under an electric field. This induces polarization of the condensation product of the organosilicon compound, increasing the relative dielectric constant ε r can be further increased.

[0032] The materials constituting the toner will be described below. <Organosilicon compounds> The organosilicon polymer complex present on the surface of the toner base particle contains a condensation product of an organosilicon compound. The content of the organosilicon compound is preferably 10 parts by mass to 20 parts by mass per 100.0 parts by mass of the toner base particle. The organosilicon compound is not particularly limited and may be any known organosilicon compound. In particular, it is preferable that the organosilicon compound be condensed to form an organosilicon polymer having a structure represented by the following formula (I): R-SiO 3 / 2 (I) (In formula (I), R represents an alkyl group (preferably having 1 to 8 carbon atoms, more preferably 1 to 6 carbon atoms). , an alkenyl group (preferably having 1 to 6 carbon atoms, more preferably 1 to 4 carbon atoms), an acyl group having 1 to 6 carbon atoms, more preferably 1 to 4 carbon atoms; More preferably, it represents an aryl group or a methacryloxyalkyl group having a carbon number of 6 to 10.

[0033] Formula (I) indicates that the condensation product of the organosilicon compound has an organic group and a silicon polymer part. As a result, in the condensation product of the organosilicon compound containing the structure represented by formula (I), the organic group has affinity with the toner mother particles, and is strongly fixed to the toner mother particles. In addition, as shown in formula (I), the organosilicon compound is condensed and the strength is increased, so that the toner has excellent durability and can be prevented from chipping or cracking and becoming deformed. In formula (I), R is preferably an alkyl group having 1 to 6 carbon atoms, such as a methyl group, a propyl group, or a normal hexyl group, a vinyl group, a phenyl group, or a methacryloxypropyl group, and the carbon number is preferably 1 to 6. More preferably, it is an alkyl group or a vinyl group with an integer of 1 to 6. An organosilicon polymer having the above structure has both hardness and flexibility due to the controlled molecular mobility of the organic group, so that toner deterioration is suppressed even when used over a long period of time, and excellent performance is exhibited.

[0034] The organosilicon compound for obtaining the organosilicon polymer can be any known organosilicon compound without any particular limitation, and is preferably at least one selected from the group consisting of organosilicon compounds represented by the following formula (II): R-Si-Ra 3 (II) In formula (II), each Ra independently represents a halogen atom or an alkoxy group (preferably having 1 to 4 carbon atoms, more preferably 1 to 3 carbon atoms); each R independently represents an alkyl group (preferably having 1 to 8 carbon atoms, more preferably 1 to 6 carbon atoms), an alkenyl group (preferably having 1 to 6 carbon atoms, more preferably 1 to 4 carbon atoms), an aryl group (preferably having 6 to 14 carbon atoms, more preferably an aryl group having 6 to 10 carbon atoms, an aryl group having 1 to 6 carbon atoms, more preferably 1 to 4 carbon atoms, represents a silyl group or a methacryloxyalkyl group.

[0035] Specific examples of the organosilicon compound represented by formula (II) include trifunctional methylsilane compounds such as methyltrimethoxysilane, methyltriethoxysilane, methyldiethoxymethoxysilane, and methylethoxydimethoxysilane; trifunctional silane compounds such as ethyltrimethoxysilane, ethyltriethoxysilane, propyltrimethoxysilane, propyltriethoxysilane, butyltrimethoxysilane, butyltriethoxysilane, hexyltrimethoxysilane, and hexyltriethoxysilane; and trifunctional phenylsilane compounds such as phenyltrimethoxysilane and phenyltriethoxysilane. trifunctional vinyl silane compounds such as vinyltrimethoxysilane and vinyltriethoxysilane; trifunctional allyl silane compounds such as allyltrimethoxysilane, allyltriethoxysilane, allyldiethoxymethoxysilane and allylethoxydimethoxysilane; trifunctional γ-methacryloxypropyl silane compounds such as γ-methacryloxypropyl trimethoxysilane, γ-methacryloxypropyl triethoxysilane, γ-methacryloxypropyl diethoxymethoxysilane and γ-methacryloxypropyl ethoxydimethoxysilane; and trifunctional silane compounds such as γ-methacryloxypropyl trimethoxysilane, γ-methacryloxypropyl triethoxysilane, γ-methacryloxypropyl diethoxymethoxysilane and γ-methacryloxypropyl ethoxydimethoxysilane.

[0036] In formula (II), R is a group having one or more carbon atoms, such as a methyl group, a propyl group, or a normal hexyl group. Preferably, Ra is an alkyl group having a carbon number of 1 to 6, a vinyl group, a phenyl group, or a methacryloxypropyl group, and more preferably an alkyl group having a carbon number of 1 to 6 or a vinyl group. This makes it possible to obtain an organosilicon polymer that satisfies the preferred range of formula (I) above. Furthermore, if Ra is an alkoxy group, this is preferred because it has appropriate reactivity in an aqueous medium and therefore makes it possible to obtain an organosilicon polymer in a stable manner, and in particular, it is more preferred that Ra is a methoxy group or an ethoxy group.

[0037] <Binding resin> The toner base particles contain a binder resin. As the binder resin, known resins can be used without any particular limitation. Specific examples include vinyl resins, polyester resins, polyurethane resins, and polyamide resins. The binder resin preferably contains a vinyl resin. Polymerizable monomers that can be used to manufacture the vinyl resin include styrene monomers such as styrene and α-methylstyrene; acrylic acid esters such as methyl acrylate and butyl acrylate; methacrylic acid esters such as methyl methacrylate, 2-hydroxyethyl methacrylate, t-butyl methacrylate, and 2-ethylhexyl methacrylate; unsaturated carboxylic acids such as acrylic acid and methacrylic acid; unsaturated dicarboxylic acids such as maleic acid; unsaturated dicarboxylic anhydrides such as maleic anhydride; nitrile vinyl monomers such as acrylonitrile; halogen-containing vinyl monomers such as vinyl chloride; and nitro vinyl monomers such as nitrostyrene. nyl monomers; and the like.

[0038] <Coloring agent> The toner base particles may contain a colorant. As the colorant, known pigments and dyes of black, yellow, magenta, cyan, and other colors, magnetic materials, and the like can be used without any particular limitation. Black colorants include black pigments such as carbon black.

[0039] Examples of yellow colorants include yellow pigments and yellow dyes such as monoazo compounds, disazo compounds, condensed azo compounds, isoindolinone compounds, benzimidazolone compounds, anthraquinone compounds, azo metal complexes, methine compounds, and allylamide compounds.Specific examples include CI Pigment Yellow 74, 93, 95, 109, 111, 128, 155, 174, 180, 185, and CI Solvent Yellow 162.

[0040] Examples of magenta colorants include magenta pigments and magenta dyes such as monoazo compounds, condensed azo compounds, diketopyrrolopyrrole compounds, anthraquinone compounds, quinacridone compounds, basic dye lake compounds, naphthol compounds, benzimidazolone compounds, thioindigo compounds, and perylene compounds.Specific examples include CI Pigment Red 2, 3, 5, 6, 7, 23, 48:2, 48:3, 48:4, 57:1, 81:1, 122, 144, 146, 150, 166, 169, 177, 184, 185, 202, 206, 220, 221, 238, 254, 269, and CI Pigment Violet 19.

[0041] Examples of cyan colorants include cyan pigments and cyan dyes such as copper phthalocyanine compounds and their derivatives, anthraquinone compounds, and basic dye lake compounds. Specific examples include CI Pigment Blue 1, 7, 15, 15:1, 15:2, 15:3, 15: 4, 60, 62, 66, etc. The content of the colorant is preferably 1.0 part by mass or more and 20.0 parts by mass or less with respect to 100.0 parts by mass of the binder resin or the polymerizable monomer.

[0042] <Wax> The toner base particles may contain a wax. As the wax, known waxes can be used without any particular limitation. Specifically, esters of monohydric alcohols and monocarboxylic acids such as behenyl behenate, stearyl stearate, palmityl palmitate, etc.; esters of dihydric carboxylic acids and monoalcohols such as dibehenyl sebacate; esters of dihydric alcohols and monocarboxylic acids such as ethylene glycol distearate, hexanediol dibehenate, etc.; esters of trihydric alcohols and monocarboxylic acids such as glycerin tribehenate; esters of tetrahydric alcohols and monocarboxylic acids such as pentaerythritol tetrastearate, pentaerythritol tetrapalmitate, etc.; dipentaerythritol hexastearate, ... Examples of such waxes include esters of hexahydric alcohols such as tall hexapalmitate and monocarboxylic acids; esters of polyfunctional alcohols such as polyglycerin behenate and monocarboxylic acids; natural ester waxes such as carnauba wax and rice wax; petroleum-based hydrocarbon waxes and their derivatives such as paraffin wax, microcrystalline wax, and petrolatum; hydrocarbon waxes and their derivatives produced by the Fischer-Tropsch process; polyolefin-based hydrocarbon waxes and their derivatives such as polyethylene wax and polypropylene wax; higher aliphatic alcohols; fatty acids such as stearic acid and palmitic acid; and acid amide waxes.

[0043] The wax content is 100.0 parts by mass of binder resin or polymerizable monomer from the viewpoint of releasability. The amount of the component (I) is preferably 1.0 parts by mass or more and 30.0 parts by mass or less, and more preferably 5.0 parts by mass or more and 20.0 parts by mass or less.

[0044] <Charge control agent> The toner may contain a charge control agent. As the charge control agent, known charge control agents can be used without any particular limitation. Specifically, as the negative charge control agent, the following metal compounds of aromatic carboxylic acids such as salicylic acid, alkyl salicylic acid, dialkyl salicylic acid, naphthoic acid, and dicarboxylic acid, or polymers or copolymers having the metal compounds of the aromatic carboxylic acids, may be used. Polymers or copolymers having sulfonic acid groups, sulfonate groups or sulfonate ester groups Examples of the suitable azo dyes or pigments include polymers, metal salts or metal complexes of azo dyes or azo pigments, boron compounds, silicon compounds, and calixarenes.

[0045] The content of the charge control agent is 0.0 with respect to 100.0 parts by mass of the binder resin or polymerizable monomer. It is preferably 1 part by mass or more and 5.0 parts by mass or less.

[0046] <External additives> The toner particles have excellent properties such as excellent fluidity even in the absence of external additives, due to the presence of the organosilicon polymer composite. However, for the purpose of further improvement, external additives may be added to the toner particles. As the external additive, any conventionally known external additive can be used without any particular limitation. Specifically, examples include raw silica fine particles such as wet-processed silica and dry-processed silica, or silica fine particles obtained by subjecting the raw silica fine particles to a surface treatment with a treatment agent such as a silane coupling agent, a titanium coupling agent, or silicone oil; and resin fine particles such as vinylidene fluoride fine particles and polytetrafluoroethylene fine particles. The content of the external additive is 0.1 parts by mass or more and 5.0 parts by mass or less relative to 100.0 parts by mass of the toner particles. is preferred.

[0047] Next, a method for producing the toner will be described below. The method for producing the toner is not particularly limited, and any known method can be used. It is preferable to produce the toner base particles in an aqueous medium and form an organosilicon polymer composite on the surface of the toner base particles. <Production process of toner base particles> The method for producing the toner base particles is not particularly limited, and may be a suspension polymerization method, a dissolution suspension method, an emulsion aggregation method, a pulverization method, or the like. Among these, the suspension polymerization method is preferable. As an example, a method for obtaining the toner base particles by the suspension polymerization method is described below. First, a polymerizable monomer capable of producing a binder resin and various additives as necessary are mixed, and the materials are dissolved or dispersed using a disperser to prepare a polymerizable monomer composition. Examples of the various additives include colorants, waxes, charge control agents, polymerization initiators, and chain transfer agents. Examples of the disperser include homogenizers, ball mills, colloid mills, and ultrasonic dispersers. Next, the polymerizable monomer composition is added to an aqueous medium containing poorly water-soluble inorganic fine particles, and droplets of the polymerizable monomer composition are prepared using a high-speed disperser such as a high-speed stirrer or an ultrasonic disperser (granulation process).

[0048] Thereafter, the polymerizable monomer in the droplets is polymerized to obtain toner base particles (polymerization step). The polymerization initiator may be mixed when preparing the polymerizable monomer composition, or may be mixed into the polymerizable monomer composition immediately before forming droplets in the aqueous medium. In addition, a polymerization initiator may be mixed into the polymerizable monomer or other solvent as necessary during or after the granulation of the droplets, i.e., immediately before starting the polymerization reaction. It can also be added in dissolved form.

[0049] In order to remove unreacted polymerizable monomers and the like from the resin particle dispersion liquid after the polymerization step, volatile components may be removed (distillation step). The heating conditions are appropriately adjusted in consideration of the vapor pressure of the components to be removed, such as the polymerizable monomer, and the removal can be performed under normal pressure or reduced pressure. After the distillation step is completed, a cooling step may be carried out to lower the liquid temperature. Depending on the conditions of the cooling step, the crystalline state and the location of the wax in the toner can be controlled.

[0050] <Process for forming organosilicon polymer composite> The organosilicon polymer composite is composed of a condensate of an organosilicon compound and a metal compound. A method for forming a condensate of an organosilicon compound on the surface of a toner base particle includes a method for condensing an organosilicon compound in an aqueous medium in which the toner base particle is dispersed. Another method includes a dry or wet method for attaching an organosilicon polymer to the toner base particle by mechanical external force. Among these, the method for condensing an organosilicon compound in an aqueous medium in which the toner base particle is dispersed is preferred because it is possible to firmly fix the condensate of the organosilicon compound to the toner base particle.

[0051] In this method, from the viewpoint of easy control of the condensation reaction and reducing the amount of the organosilicon compound remaining in the toner base particle dispersion liquid, it is preferable to hydrolyze the organosilicon compound before adding it to the aqueous medium. Furthermore, when hydrolyzing the organosilicon compound, a metal compound is put into the organosilicon compound, and the organosilicon compound is hydrolyzed while stirring, and the organosilicon compound is condensed on the surface of the metal compound to perform surface treatment. In this way, when the hydrolyzed liquid of the organosilicon compound containing the metal compound is put into the aqueous medium, an organosilicon polymer composite is formed in which the metal compound is encapsulated on the surface of the toner base particle. In this case, the ratio of the organosilicon compound to the metal compound is preferably 40:0.30 to 40:6.00 (parts by mass).

[0052] That is, the toner manufacturing method preferably includes the steps of: introducing a polymerizable monomer composition into an aqueous medium containing poorly water-soluble inorganic fine particles, and preparing droplets of the polymerizable monomer composition using a high-speed disperser such as a high-speed stirrer or an ultrasonic disperser (granulation step), polymerizing the polymerizable monomer in the droplets to obtain toner base particles (polymerization step), and condensing an organosilicon compound in the aqueous medium in which the toner base particles are dispersed (organosilicon polymer composite formation step).

[0053] Hydrolysis is preferably carried out in an aqueous medium with pH adjusted using known acid and base.It is known that the hydrolysis of organosilicon compounds is pH-dependent, and the pH of the hydrolysis is preferably appropriately changed according to the type of organosilicon compound.For example, when methyltriethoxysilane is used as the organosilicon compound, the pH of the aqueous medium is preferably 2.0 or more and 6.0 or less. The temperature during hydrolysis is preferably 40° C. to 70° C., and the time is preferably 30 minutes to 180 minutes.

[0054] Specific examples of acids for adjusting the pH include inorganic acids such as hydrochloric acid, hydrobromic acid, hydroiodic acid, hypochlorous acid, chlorous acid, chloric acid, perchloric acid, hypobromous acid, bromous acid, bromic acid, perbromic acid, hypoiodous acid, iodous acid, iodic acid, periodic acid, sulfuric acid, nitric acid, phosphoric acid, and boric acid, and organic acids such as acetic acid, citric acid, formic acid, gluconic acid, lactic acid, oxalic acid, and tartaric acid.

[0055] Specific examples of bases for adjusting the pH include the following: alkali metal hydroxides such as potassium hydroxide, sodium hydroxide, and lithium hydroxide, and aqueous solutions thereof; alkali metal carbonates such as potassium carbonate, sodium carbonate, and lithium carbonate, and aqueous solutions thereof; alkali metal sulfates such as potassium sulfate, sodium sulfate, and lithium sulfate, and aqueous solutions thereof; alkali metal phosphates such as potassium phosphate, sodium phosphate, and lithium phosphate, and aqueous solutions thereof; and alkaline earth metal hydroxides such as calcium hydroxide and magnesium hydroxide. hydroxides and their aqueous solutions, ammonia, and amines such as triethylamine.

[0056] In the process of forming the organosilicon polymer composite, the pH when the metal compound and the organosilicon compound (or its hydrolysate) are mixed with the toner base particle dispersion is preferably a pH at which condensation of the organosilicon compound does not easily proceed, for example, 2.0 to 6.0 is preferable, and 4.0 to 6.0 is more preferable. It is preferable to mix the metal compound and the organosilicon compound (or its hydrolysate) with the toner base particle dispersion and control the pH. The process of forming the organosilicon polymer composite is preferably pH 8.5 to 10.5, and more preferably pH 9.0 to 10.0.

[0057] In addition, metal compounds generally tend to aggregate more easily as the particle size becomes smaller, making it difficult to perform uniform surface treatment. If the surface treatment is not performed uniformly, the metal compound is likely to be exposed from the surface of the organosilicon polymer composite. For this reason, the number-average particle size of the metal compound is preferably 10 nm or more, and more preferably 20 to 35 nm.

[0058] The ME, MX, and MN can be arbitrarily controlled by adjusting the conditions such as the particle size and the amount added of each material. Specifically, the ME can be increased by decreasing the particle size of the metal compound particles, whereas the ME can be decreased by increasing the particle size of the metal compound particles. MX can be increased by increasing the amount of the metal compound or decreasing the amount of the organosilicon compound. MX can be decreased by decreasing the amount of the metal compound or increasing the amount of the organosilicon compound. Also, MN can be increased by increasing the particle size of the metal compound, and MN can be decreased by decreasing the particle size of the metal compound.

[0059] <Solid-liquid separation process, washing process, and drying process> The toner particle dispersion may be treated with an acid or alkali in order to remove the dispersion stabilizer attached to the surface of the toner particles. After removing the dispersion stabilizer from the toner particles, the toner particles are separated from the aqueous medium by a general solid-liquid separation method. In order to completely remove the acid or alkali and the dispersion stabilizer component dissolved therein, it is preferable to add water again to wash the toner particles. This washing process is repeated several times, and after sufficient washing, the toner particles can be obtained by solid-liquid separation again. The obtained toner particles may be dried by a known drying means if necessary.

[0060] The weight average particle size of the obtained toner particles is preferably from 3 μm to 10 μm, and more preferably from 4 μm to 8 μm. The weight average particle size of the toner particles can be controlled by the amount of dispersion stabilizer added in the granulation process.

[0061] <External addition process> An external additive may be added to the obtained toner particles for the purpose of improving fluidity, chargeability, blocking property, etc. The external addition step is carried out by putting the external additive and the toner particles into a mixer such as an FM mixer (manufactured by Nippon Coke & Engineering Co., Ltd.) and thoroughly mixing them.

[0062] Next, the measurement methods for each physical property will be described. <Method for measuring the ratio (ME) of the number of specific metal atoms to the sum of the numbers of carbon atoms, oxygen atoms, silicon atoms, and specific metal atoms> The following apparatus is used under the following conditions to perform elemental analysis of the toner surface, and the obtained values ​​are analyzed to calculate the above atomic number ratio. Measurement device: Quantum2000 (product name, manufactured by ULVAC-PHI, Inc.) ·X-ray source: Al Kα ·Xray Setting:100μmφ(25W(15KV)) Photoelectron take-off angle: 45 degrees Neutralization gun: 20μA, 1V Ar ion gun: 7mA, 10V Sweep number: Si 30 times, C 10 times, O 20 times, Ti 50 times, Al 50 times, Zr 50 times ·Analysis area: 300×200μm Pass Energy: 58.70eV Step size: 1.25eV Analysis software: Maltipak (PHI)

[0063] From the measured peak intensity of each element, the atomic concentration (atomic %) of each element is calculated using the relative sensitivity factor provided by PHI. Based on the calculation result, the ratio of the number of specific metal atoms to the sum of the numbers of carbon atoms, oxygen atoms, silicon atoms, and specific metal atoms is calculated. Note that when two or more types of specific metal atoms are contained, the ratio of the sum of the numbers of those metal atoms is calculated. That is, ME=(sum of the number of specific metal atoms) / (sum of the number of carbon atoms, oxygen atoms, silicon atoms, and specific metal atoms).

[0064] <Method of measuring weight average particle size (D4) and number average particle size (D1)> The weight average particle size (D4) of the toner, toner particles, or toner base particles (hereinafter, also referred to as toner, etc.) is calculated as follows. The measuring device is a precision particle size distribution measuring device "Coulter Counter" equipped with a 100 μm aperture tube and using the narrow hole electrical resistance method. The measurement conditions and the analysis of the measurement data are set using the dedicated software "Beckman Coulter Multisizer 3 Version 3.51" (Beckman Coulter, Inc.). The measurement is performed with an effective number of measurement channels of 25,000. The electrolyte solution used for the determination is prepared by dissolving special grade sodium chloride in ion-exchanged water to a concentration of 1.0%, for example, "ISOTON II" (manufactured by Beckman Coulter, Inc.). Before performing measurements and analysis, the dedicated software is set up as follows.

[0065] In the "Change standard measurement method (SOMME)" screen of the dedicated software, set the total count number in the control mode to 50,000 particles, the number of measurements to 1, and the Kd value to the value obtained using "Standard particle 10.0 μm" (Beckman Coulter, Inc.). Press the "Threshold / Noise level measurement button" to automatically set the threshold and noise level. In addition, set the current to 1,600 μA, the gain to 2, the electrolyte to ISOTON II, and check "Flush aperture tube after measurement." In the "Pulse to particle size conversion setting" screen of the dedicated software, set the bin interval to logarithmic particle size, the particle size bin to 256 particle size bin, and the particle size range to 2 μm to 60 μm.

[0066] The specific measurement method is as follows. (1) Pour 200.0 mL of the electrolyte solution into a 250 mL round-bottom glass beaker made exclusively for the Multisizer3, set it on the sample stand, and stir the stirrer rod counterclockwise at 24 revolutions per second. Then, use the "Aperture tube flush" function of the dedicated software to remove dirt and air bubbles from inside the aperture tube. (2) Put 30.0 mL of the electrolyte solution into a 100 mL flat-bottom glass beaker. Add "Contaminon N" (a 10% aqueous solution of a neutral detergent for cleaning precision measuring instruments with a pH of 7, consisting of a nonionic surfactant, an anionic surfactant, and an organic builder, manufactured by Wako Pure Chemical Industries, Ltd.) as a dispersant. ) diluted 3 times with ion-exchanged water and add 0.3 mL of the diluted solution. (3) Prepare an ultrasonic disperser "Ultrasonic Dispersion System Tetra150" (manufactured by Nikkaki Bios Co., Ltd.) that has two built-in oscillators with an oscillation frequency of 50 kHz and a phase shift of 180 degrees and an electrical output of 120 W. Place 3.3 L of ion-exchanged water in the ultrasonic disperser's water tank and add 2.0 mL of Contaminon N to this tank. (4) The beaker (2) is set in the beaker fixing hole of the ultrasonic disperser, and the ultrasonic disperser is operated. Then, the height position of the beaker is adjusted so that the resonance state of the liquid surface of the electrolyte solution in the beaker is maximized. (5) While the electrolyte solution in the beaker in (4) is being irradiated with ultrasonic waves, 10 mg of toner or the like is added little by little to the electrolyte solution and dispersed. Then, ultrasonic dispersion treatment is continued for another 60 seconds. During ultrasonic dispersion, the water temperature in the water tank is appropriately adjusted so that it is between 10°C and 40°C. (6) Using a pipette, drip the electrolytic solution (5) in which the toner or the like has been dispersed into the round-bottom beaker (1) placed in the sample stand to adjust the measurement concentration to 5%. Then, measurements are continued until the number of particles measured reaches 50,000. (7) The measurement data is analyzed using the dedicated software that comes with the device, and the weight average particle size (D4) is calculated. Note that when the dedicated software is set to Graph / Volume %, the "Average diameter" on the "Analysis / Volume Statistics (Arithmetic Mean)" screen is the weight average particle size (D4). When the dedicated software is set to Graph / Number %, the "Average diameter" on the "Analysis / Number Statistics (Arithmetic Mean)" screen is the number average particle size (D1).

[0067] <Measurement of the ratio (MX) of the number of specific metal atoms to the total number of silicon atoms and specific metal atoms in the region outside the contour of the toner base particle> - Preparation of toner flake samples The toner is spread on a cover glass (Matsunami Glass Co., Ltd., square cover glass No. 1) so that it becomes a single layer, and an Os film (5 nm) and a naphthalene film (20 nm) are applied to the toner as a protective film using an osmium plasma coater (Filgen Co., Ltd., OPC80T). Next, a PTFE tube (inner diameter 1.5 mm × outer diameter 3 mm × 3 mm) is filled with photocurable resin D800 (JEOL Co., Ltd.), and the cover glass is gently placed on top of the tube so that the toner is in contact with the photocurable resin D800. In this state, the resin is irradiated with light to harden it, and then the cover glass and tube are removed to form a cylindrical resin with toner embedded in its outermost surface. Using an ultrasonic ultramicrotome (Leica, UC7), a cutting speed of 0.6 mm / s is used to cut the length of the toner radius (4.0 μm when the weight average particle size (D4) is 8.0 μm) from the outermost surface of the cylindrical resin to expose the cross section of the toner. Next, cutting is performed to a film thickness of 100 nm, and a thin sample of the toner cross section is produced. By cutting in this manner, a cross section of the center of the toner can be obtained.

[0068] Observation of toner cross section and EDS analysis The above thin sample was observed in STEM mode of a scanning transmission electron microscope (JEOL, JEM2800) connected to an EDS analyzer (energy dispersive X-ray analyzer) at a magnification of 400,000 times, in a field of view where the outermost surface of the toner could be confirmed. The constituent elements of the cross-section of the observed toner were collected by an EDS analyzer to obtain a spectrum, and an EDS mapping image was prepared. Spectral collection and analysis were performed using an NSS (Thermo Fischer Scientific). The collection conditions were an acceleration voltage of 200 kV, a probe size of 1.0 nm or 1.5 nm appropriately selected so that the dead time was 15 to 30, a mapping resolution of 256 x 256, and a frame number of 500. EDS mapping images were obtained for 30 cross-sections of the toner.

[0069] Analysis of EDS mapping images By analyzing the EDS mapping image obtained as described above, the ratio of the number of specific metal atoms to the number of silicon atoms in the organosilicon polymer composite can be calculated. First, press the "Extract from line" button in NSS and select the analysis range freehand. Specifically, trace the interface between the toner base particle and the organosilicon polymer composite present on the surface of the toner base particle to draw a baseline, and then draw a parallel line 200 nm away from the baseline toward the outer edge of the toner. In this way, the range between the baseline and the parallel line is selected as the analysis range, and this range is the area outside the outline of the toner base particle.

[0070] Once the toner analysis range has been selected, pressing the "Spectrum Quantitation" button will automatically calculate the silicon atom concentration and specific metal atom concentration (atomic %) in the selected range. At this time, silicon and specific metal elements are selected as the elements to be analyzed. Based on the values ​​of the silicon atom concentration (atomic %) and specific metal atom concentration (atomic %) displayed in the quantification results, the ratio MX of the number of specific metal atoms in the sum of the number of silicon atoms and the number of specific metal atoms in the organosilicon polymer composite can be calculated. Note that when two or more types of specific metal atoms are contained, the ratio of the sum of the numbers of silicon atoms and those specific metal atoms to the sum of the numbers of those specific metal atoms is taken. That is, MX=(sum of the number of specific metal atoms) / (sum of the number of silicon atoms and the number of specific metal atoms). The arithmetic average value of 30 cross sections of the toner is used.

[0071] <Number average diameter of domains of metal compounds> In the same manner as in <Measurement of the ratio (MX) of the number of specific metal atoms to the sum of the numbers of silicon atoms and specific metal atoms in the region outside the contour of the toner base particle>, a thin toner sample was prepared and the cross section of the toner was observed and analyzed with EDS. Analysis of EDS mapping images (calculation of the number-average diameter of domains) The primary particle size of the EDS mapping image of the specific metal atom obtained as described above was measured using the image processing software "Image-Pro Plus (Media Cybernetics)". First, use the straight line tool (Straight Line) on the toolbar to select the scale bar displayed at the bottom of the STEM image. In this state, select Set Scale from the Analyze menu to open a new window and enter the pixel distance of the selected line in the Distance in Pixels field. Enter the scale bar value (e.g., 100) in the Known Distance field of the window, enter the unit of the scale bar (nm) in the Unit of Measurement field, and click OK to complete the scale setting. Next, adjust the contrast so that only the specific metal compound is selected, and perform binarization. The area A (nm ) of each domain of the specific metal compound on the obtained binarized image is calculated. 2 ) was calculated, and each domain diameter Dn (nm) was calculated using the following formula (3). The above analysis was performed for 30 EDS mapping images. Dn = (4A / π) 1 / 2 (3) Of the calculated domain diameters Dn, those having a diameter of 10 nm or more were extracted, and the average diameter of these was taken as the number-average diameter of the domains of the metal compound.

[0072] <How to confirm organosilicon polymer> The organosilicon polymer on the surface of the toner base particle is confirmed by comparing the ratio of the elemental contents (atomic %) of Si and O (Si / O ratio) with a standard. Standards of the organosilicon polymer and silica fine particles are subjected to EDS analysis under the conditions described in <Measurement of the ratio (MX) of the number of specific metal atoms to the sum of the numbers of silicon atoms and specific metal atoms in the region outside the outline of the toner base particle> to obtain the atomic concentrations (atomic %) of silicon and oxygen. The ratio of the silicon atomic concentration to the oxygen atomic concentration (Si / O) of the organosilicon polymer is defined as A. The ratio of silicon atom concentration to oxygen atom concentration (Si / O) of the silica microparticles is represented as B. The standard sample is measured 10 times under the same conditions, and the arithmetic mean values ​​for A and B are obtained. The cross section of the toner is observed under the conditions described in <Measurement of the ratio (MX) of the number of specific metal atoms to the sum of the numbers of silicon atoms and specific metal atoms in the area outside the contour of the toner base particle>, and if the Si / O ratio of the part where silicon is detected is closer to A than [(A+B) / 2], that part is judged to be an organosilicon polymer. Tospearl 120A (Momentive Performance Materials Japan, LLC) is used as a sample of organosilicon polymer particles, and HDK V15 (Asahi Kasei) is used as a sample of silica fine particles.

[0073] <How to check titanium dioxide particles> Whether the metal compound is titanium dioxide or not is confirmed by EDS analysis under the conditions described in <Measurement of the ratio (MX) of the number of specific metal atoms in the sum of the number of silicon atoms and specific metal atoms in the area outside the outline of the toner base particle>. In the measured EDS mapping image, press the "Extract from line" button of NSS and select the range of the metal compound part by freehand. Once the analysis range of the toner is selected, press the "Spectrum quantification" button and the concentration of each atom (atomic %) in the selected range is automatically calculated. Identification is performed by comparing the ratio (O / Ti) of the oxygen atomic concentration (atomic %) to the titanium atomic concentration (atomic %) displayed in the quantification result with the standard. The titanium dioxide standard used is Fujifilm Wako Pure Chemical Corporation (CAS.No: 1317-80-2).

[0074] <Calculation method for the coverage rate of toner base particles with organosilicon polymer composite> The coverage rate of the toner base particles by the organosilicon polymer composite is calculated by processing a toner surface image taken with a field emission scanning electron microscope (FE-SEM) after removing external additives and weakly adhered metal compounds and organosilicon polymers.

[0075] -Removal of external additives from toner particles Add 160 g of sucrose (Kishida Chemical Co., Ltd.) to 100 mL of ion-exchanged water and dissolve in a hot water bath to prepare a 61.5% by mass sucrose aqueous solution. Add 31.0 g of the above sucrose aqueous solution and 6.0 g of Contaminon N (trade name) (a 10.0% by mass aqueous solution of a neutral detergent for cleaning precision measuring instruments, pH 7, consisting of a nonionic surfactant, an anionic surfactant, and an organic builder, manufactured by Wako Pure Chemical Industries, Ltd.) to a centrifuge tube (50 mL) to prepare a dispersion. Add 1.0 g of toner to this dispersion, and break up the toner clumps with a spatula or the like. The centrifuge tube is shaken at 300 spm (strokes per minute) in a shaker (AS-1N manufactured by AS ONE Co., Ltd.) equipped with an optional centrifuge sedimentation tube holder for universal shakers (AS ONE Co., Ltd.). The solution is shaken at 3500 rpm for 20 minutes at a speed of 4 cm per minute. After shaking, the solution is transferred to a glass tube (50 mL) for a swing rotor and separated in a centrifuge at 3,500 rpm for 30 minutes. Visually check that the toner and aqueous solution are sufficiently separated, and collect the toner that has separated into the top layer with a spatula or similar. The collected toner is filtered through a vacuum filter and then dried in a dryer for at least 1 hour. The dried product is crushed with a spatula to obtain toner (a).

[0076] · Processing to remove weakly adhered metal compounds and organosilicon polymers from toner particles A dispersion is prepared by adding 31.0 g of the sucrose aqueous solution and 6.0 g of the Contaminon N to a centrifuge tube. 1.0 g of the toner treated with treatment (a) is added to this dispersion, and the toner clumps are broken down using a spatula or the like. Using a TAITEC VP-050, ultrasonic waves with an electrical output of 120 W are applied to the centrifuge tube for 10 minutes. After ultrasonic treatment, the solution is transferred to a glass tube for a swing rotor (50 mL) and separated in a centrifuge at 3500 rpm for 30 minutes. Visually confirm that the toner treated with ultrasonic treatment and the aqueous solution are sufficiently separated, and the toner separated to the top layer is collected using a spatula or the like. The collected toner is filtered through a vacuum filter and then dried in a dryer for at least one hour. The dried product is crushed with a spatula to obtain toner (b).

[0077] The coverage of the toner base particles with the organosilicon polymer composite is calculated by analyzing toner surface images taken with a field emission scanning electron microscope S-4800 (Hitachi High-Technologies Corporation) using image analysis software Image-Pro Plus ver.5.0 (Nippon Roper Co., Ltd.). The image taking method for the S-4800 is as follows.

[0078] (1) Sample preparation Apply a thin layer of conductive paste to a sample stage (aluminum sample stage 15 mm x 6 mm), then spray the toner treated in step (b) onto the paste. Then, use air to remove excess toner from the sample stage and dry thoroughly. Set the sample stage in the sample holder, and adjust the sample stage height to 36 mm using the sample height gauge.

[0079] (2) S-4800 observation condition setting The coverage is calculated using the image obtained by observing the backscattered electron image of the S-4800. Backscattered electron images have less charge-up of fine particles including metal compounds than secondary electron images, so they can be measured with high accuracy. Pour liquid nitrogen into the anti-contamination trap attached to the S-4800 housing until it overflows, and leave it for 30 minutes. Start the S-4800's "PC-SEM" and perform flushing (cleaning the FE chip, which is the electron source). Click the accelerating voltage display area on the control panel on the screen, and press the [Flushing] button to open the flushing execution dialog. Check that the flushing intensity is 2 and execute it. Check that the emission current due to flushing is 20 to 40 μA. Insert the sample holder into the sample chamber of the S-4800 housing. Press [Origin] on the control panel to move the sample holder to the observation position. Click the accelerating voltage display to open the HV setting dialog, and set the accelerating voltage to [0.8kV] and the emission current to [20μA]. In the [Basic] tab of the operation panel, set the signal selection to [SE], select the SE detector to [Upper (U)] and [+BSE], and select [LA100] in the selection box to the right of [+BSE] to set the mode to observation with backscattered electron images. In the same [Basic] tab of the operation panel, set the probe current in the electron optical system condition block to [Normal], the focus mode to [UHR], and the WD to [3.0mm]. Press the [ON] button in the accelerating voltage display of the control panel to apply the accelerating voltage.

[0080] (3) Aperture alignment adjustment Drag within the magnification display area on the control panel to set the magnification to 5,000 (5k). Rotate the focus knob [COARSE] on the operation panel to adjust the aperture alignment once the image is in focus to a certain extent. Click [Align] on the control panel to display the alignment dialog and select [Beam]. Rotate the STIGMA / ALIGNMENT knobs (X, Y) on the operation panel to move the displayed beam to the center of the concentric circles. Next, select [Aperture] and rotate the STIGMA / ALIGNMENT knobs (X, Y) one by one to stop the image movement or adjust it so that it moves as little as possible. Close the aperture dialog and use autofocus to adjust the focus. Repeat this operation two more times to adjust the focus.

[0081] (4) Focus adjustment Drag within the magnification display area of ​​the control panel to set the magnification to 10,000 (10k). Rotate the focus knob [COARSE] on the operation panel to adjust the aperture alignment again once the image is in focus to a certain extent. Click [Align] on the control panel to display the alignment dialog box and select [Beam]. Rotate the STIGMA / ALIGNMENT knobs (X, Y) on the operation panel to move the displayed beam to the center of the concentric circles. Next, select [Aperture] and rotate the STIGMA / ALIGNMENT knobs (X, Y) one by one to stop the image movement or adjust it so that it moves as little as possible. Close the Aperture dialog and adjust the focus with autofocus. After that, set the magnification to 50,000 (50k) times, adjust the focus using the focus knob and STIGMA / ALIGNMENT knob as above, and then adjust the focus with autofocus again. Repeat this operation to adjust the focus. Here, if the tilt angle of the observation surface is large, the measurement accuracy of the coverage rate is likely to be low, so when adjusting the focus, select one that brings the entire observation surface into focus at the same time, and select one with as little surface tilt as possible for analysis.

[0082] (5) Image storage Adjust the brightness in ABC mode, take a photo with a size of 640 x 480 pixels, and save it. Use this image file to perform the following analysis. Take one photo for each toner particle, and obtain images for at least 30 toner particles.

[0083] (6) Image analysis The image obtained by the above method is binarized using the following analysis software to calculate the coverage. At this time, the above screen is divided into 12 squares and each is analyzed. The analysis conditions for the image analysis software Image-Pro Plus ver.5.1J (MediaCyber ​​Netic) are as follows.

[0084] Software Image-ProPlus5.1J From the toolbar, select "Measurement", then "Count / Size", then "Options", and set the binarization conditions. In the object extraction options, select 8 connectivity and set smoothing to 0. In addition, do not select pre-selection, fill holes, or inclusion lines, and set "Exclude borders" to "None". From the toolbar, select "Measurement item", and set the area selection range to 2~10. 7Enter the following. To calculate the coverage rate, a square area is enclosed and the area (C) of the area should be 25,000 pixels. Perform automatic binarization using "Processing"-Binarization. When binarized, the organosilicon polymer composite appears as a white contrast, and the toner base particle surface appears as a black contrast. Calculate the total area of ​​the toner base particle surface (D). The coverage rate a can be found from the area C of the square area and the total area D of the toner base particle surface using the following formula. Coverage rate a(%)=100-((D / C)×100) As described above, the coverage ratio a is calculated for 30 or more particles of toner that have been subjected to the treatment (b). The average value of all the obtained data is taken as the coverage ratio. EXAMPLES

[0085] The present disclosure will be specifically described with reference to the following examples. However, the present invention is not limited to these examples. In the formulations of the examples and comparative examples, "parts" and "%" are all by mass unless otherwise specified.

[0086] <Production Example of Toner Base Particle Dispersion 1> 11.2 parts of sodium phosphate (12-hydrate) was added to a reaction vessel containing 390.0 parts of ion-exchanged water, and the mixture was kept at 65°C for 1.0 hours while purging with nitrogen. The mixture was stirred at 12000 rpm using a TK homomixer (manufactured by Tokushu Kika Kogyo Co., Ltd.). While maintaining the stirring, an aqueous calcium chloride solution in which 7.4 parts of calcium chloride (2-hydrate) was dissolved in 10.0 parts of ion-exchanged water was added to the reaction vessel all at once to prepare an aqueous medium containing a dispersion stabilizer. Furthermore, 1.0 mol / L of hydrochloric acid was added to the aqueous medium in the reaction vessel to adjust the pH to 6.0, and aqueous medium 1 was prepared.

[0087] (Preparation of Polymerizable Monomer Composition) Styrene 60.0 parts ·CIPigment Blue15:3 6.3 parts The above materials were placed in an attritor (manufactured by Nippon Coke & Engineering Co., Ltd.), and further dispersed using zirconia particles having a diameter of 1.7 mm at 220 rpm for 5.0 hours to prepare a colorant dispersion in which the pigment was dispersed.

[0088] The following materials were then added to the colorant dispersion: Styrene 15.0 parts ・25.0 parts n-butyl acrylate Polyester resin 5.0 parts (Polymerization product of terephthalic acid and 2 moles of propylene oxide adduct of bisphenol A, weight average molecular weight Mw=10000, acid value: 8.2mgKOH / g) HNP9 (melting point: 76°C, manufactured by Nippon Seiro Co., Ltd.) 6.0 parts The above materials were kept at 65° C. and uniformly dissolved and dispersed at 500 rpm using a TK homomixer to prepare a polymerizable monomer composition.

[0089] (granulation process) While maintaining the temperature of the aqueous medium 1 at 70° C. and the rotation speed of the stirring device at 12,500 rpm, the polymerizable monomer composition was charged into the aqueous medium 1, and 8.0 parts of t-butyl peroxypivalate as a polymerization initiator was added. Granulation was continued for 10 minutes while maintaining the stirring device at 12,500 rpm.

[0090] (Polymerization process) The high-speed stirring device was changed to a stirrer equipped with a propeller stirring blade, and polymerization was carried out for 5.0 hours while maintaining 70°C while stirring at 200 rpm, and then the temperature was raised to 85°C and heated for 2.0 hours to carry out a polymerization reaction. The temperature was then raised to 98°C and heated for 3.0 hours to remove residual monomers, and ion-exchanged water was added to adjust the toner base particle concentration in the dispersion to 30.0 mass%, obtaining toner base particle dispersion 1 in which toner base particles 1 are dispersed. The number average particle diameter (D1) of toner base particles 1 was 6.2 μm, and the weight average particle diameter (D4) was 6.9 μm.

[0091] <Production Example of Toner Base Particle Dispersion Liquid 2> 11.2 parts of sodium phosphate (12-hydrate) was added to a reaction vessel containing 390.0 parts of ion-exchanged water, and the mixture was kept at 65°C for 1.0 hours while purging with nitrogen. The mixture was stirred at 12000 rpm using a TK homomixer (manufactured by Tokushu Kika Kogyo Co., Ltd.). While maintaining the stirring, an aqueous calcium chloride solution in which 7.4 parts of calcium chloride (2-hydrate) was dissolved in 10.0 parts of ion-exchanged water was added to the reaction vessel all at once to prepare an aqueous medium containing a dispersion stabilizer. Furthermore, 1.0 mol / L of hydrochloric acid was added to the aqueous medium in the reaction vessel to adjust the pH to 6.0, and aqueous medium 2 was prepared. Toner base particle dispersion 2 was obtained in the same manner as in the production example of toner base particle dispersion 1, except that aqueous medium 2 was used instead of aqueous medium 1. The number average particle size (D1) of toner base particles 2 was 5.2 μm and the weight average particle size (D4) was 6.7 μm.

[0092] <Production Example of Toner Particle 1> (Organosilicon Polymer Hydrolysis Process) 60.0 parts of ion-exchanged water was weighed into a reaction vessel equipped with a stirrer and a thermometer, and the pH was adjusted to 4.0 using 10% by mass hydrochloric acid. This was heated with stirring until the temperature reached 40°C. Then, 40.0 parts of methyltriethoxysilane, an organosilicon compound, and 1.50 parts of titanium dioxide (average primary particle size 30 nm) were added, and the mixture was stirred for 2 hours or more to carry out hydrolysis. The end point of the hydrolysis was confirmed by visual inspection when the oil and water were not separated but formed into a single layer, and the mixture was cooled. Thus, a composite liquid containing a hydrolyzate of the organosilicon compound and titanium dioxide was obtained (referred to as composite liquid 1).

[0093] (Formation of Organosilicon Polymer Composite) After the temperature of the toner base particle dispersion liquid 1 was cooled to 55°C, 13.5 parts of composite liquid 1 was added to 500 parts of the toner base particle dispersion liquid 1 to initiate polymerization of the organosilicon compound. After holding the mixture as it was for 15 minutes, the pH was adjusted to 5.5 with a 3.0% aqueous sodium bicarbonate solution. After holding the mixture at 55°C for 60 minutes while continuing to stir, the pH was adjusted to 9.5 with a 3.0% aqueous sodium bicarbonate solution, and the mixture was held for a further 240 minutes to obtain toner particle dispersion liquid 1.

[0094] (Washing and drying process) After the organosilicon polymer composite formation process was completed, toner particle dispersion 1 was cooled, hydrochloric acid was added to toner particle dispersion 1 to adjust the pH to 1.5 or less, and the mixture was left to stir for 1 hour, after which solid-liquid separation was performed using a pressure filter to obtain a toner cake. This was reslurried in ion-exchanged water to make a dispersion again, and then solid-liquid separation was performed using the aforementioned filter to obtain a toner cake. The obtained toner cake was dried in a constant temperature bath at 40°C for 72 hours and classified to obtain toner particles 1. The physical properties of toner particles 1 are shown in Table 3.

[0095] <Production Examples of Toner Particles 2 to 22> Composite liquids (composite liquids 2 to 22) containing hydrolyzates of organosilicon compounds and titanium dioxide were obtained in the same manner as in the manufacturing example of toner particles 1, except that the types and amounts of raw materials in the (organosilicon polymer hydrolysis process) were changed as shown in Table 1. Next, toner particle dispersions 2 to 22 were obtained in the same manner as in the production example of toner particle 1, except that the type, content and final pH of the composite liquid (organosilicon polymer composite formation process) were changed as shown in Table 2. The obtained toner particle dispersions 2 to 22 are each treated in the same manner as in the production example of toner particle 1 (washing and drying steps) to obtain toner particles 2 to 22. The physical properties of each are shown in Table 3.

[0096] <Production Example of Toner Particle 23> (Organosilicon Polymer Hydrolysis Process) 80.0 parts of ion-exchanged water was weighed into a reaction vessel equipped with a stirrer and a thermometer, and the pH was adjusted to 3.5 using 10% by weight hydrochloric acid. This was heated with stirring until the temperature reached 60°C. Then, 20.0 parts of methyltriethoxysilane, an organosilicon compound, was added and stirred for 1 hour to obtain an organosilicon polymer hydrolyzate.

[0097] (Formation of Organosilicon Polymer Composite) The following samples were weighed and placed in a reaction vessel, and mixed using a propeller agitator. Toner base particle dispersion liquid 2 500.0 parts 9.0 parts of hydrolyzed solution of organosilicon compounds Titanium lactate 44% aqueous solution (TC-310: Matsumoto Fine Chemical Co., Ltd.) 1.82 parts (equivalent to 0.80 parts of titanium lactate) Next, the pH of the mixture was adjusted to 7.0 using a 1 mol / L NaOH aqueous solution, and the temperature was further increased to 50° C. and then maintained for 1 hour. Thereafter, the pH was adjusted to 9.5 using a 1 mol / L NaOH aqueous solution, and the mixture was maintained for 2.0 hours with stirring.

[0098] Next, 1.0 mol / L hydrochloric acid was added to adjust the pH of the mixed solution to 7.0. 17.5 parts of the hydrolyzed solution of the organosilicon compound was added, and then 1 mol / L NaOH aqueous solution was added. The pH was adjusted to 9.5 using a solvent and the mixture was maintained for 2.0 hours with stirring to obtain toner particle dispersion 23. The same steps (washing and drying) as in the manufacturing example of the toner particle dispersion liquid 1 are carried out to obtain toner particles 23. Toner particles 23 have a titanium phosphate compound and an organosilicon polymer present in an organosilicon polymer complex, and the titanium phosphate compound is a reaction product of titanium lactate and phosphate ions derived from sodium phosphate or calcium phosphate in aqueous medium 2. The physical properties of toner particles 23 are shown in Table 3.

[0099] <Production Example of Toner Particle 24> The toner base particle dispersion 1 was used as a toner particle dispersion 24 without forming an organosilicon polymer composite, and washed and dried in the same manner as in the production example of the toner particles 1 to obtain toner particles 24.

[0100] <Toner 24 Manufacturing Example> ·Toner particles 24 100.0 parts ·Titanium dioxide particles (average primary particle diameter 30 nm) 0.035 parts ·Hydrophobic silica particles surface-treated with dimethyl silicone oil (Average primary particle size: 7nm) 1.00 parts The above materials were charged into a SUPERMIXER PICCOLO SMP-2 (manufactured by Kawata Corporation) and mixed at 3000 rpm for 20 minutes, then sieved through a mesh with 150 μm openings to obtain Toner 24.

[0101] [Table 1]

[0102] [Table 2]

[0103] [Table 3] In the table, for example, 5.0E-03 means 5.0 x 10 -3 Shows.

[0104] <Example 1> The following evaluation was carried out using the toner particles 1 as they were as toner 1. The evaluation results are shown in Table 4.

[0105] (Evaluation 1: Evaluation of fogging when talc is mixed) The evaluation was carried out using a commercially available color laser printer, HP Laserjet Enterprise Color M553dn. The toner was removed from the black toner cartridge and filled with 300g of toner and 0.3g of talc powder (Japan Talc Co., Ltd.'s general-purpose talc "PA-OG") (0.1 wt% relative to the toner). In this evaluation, talc was intentionally mixed into the cartridge to reproduce a situation that may occur in a cleaner-less system. The inclusion of talc reduces the toner's triboelectric charging properties, creating an environment in which charging control is more difficult. This cartridge was installed in the black station, and dummy cartridges were installed in the other stations, and the cartridge was left in an environment of 30.0°C / 80% RH for three days.

[0106] The printer was equipped with XEROX4200 paper (75 g / m2 ) was set, and at 30.0°C / 80% RH, a completely white image was output using paper with a sticky note attached to part of the printed surface of the image to mask it (white image 1). Then, 10,000 sheets of a character pattern image with a print rate of 4% were printed. After the 10,000 sheets were printed, a completely white image was output again using paper with a sticky note attached to part of the printed surface of the image to mask it (white image 2). After the paper was printed, the toner was consumed and the talc concentration in the cartridge increased, making charge control more difficult.

[0107] Regarding white image 1, after removing the sticky note, the part with the sticky note and the part without the sticky note were The reflectance (%) was measured at five points for each part, the average value was calculated, and the difference in the average values ​​(parts with sticky notes attached - parts without sticky notes attached) was calculated and this was taken as the initial fog. In addition, the difference in the average values ​​for white image 2 was calculated in the same way and this was taken as the fog after durability testing. (Evaluation Criteria) A: The difference in the average value is less than 0.5% B: The difference in the average value is between 0.5% and 1.5%. C: The difference in the average value is 1.5% or more and less than 3.0%. D: The difference in the average value is 3.0% or more.

[0108] (Evaluation 2: Ghost evaluation when talc is mixed) After outputting the white image 2 in Evaluation 1, one ghost evaluation image was output. The ghost evaluation image is a 15 mm x 15 mm solid image arranged in a horizontal row at 15 mm intervals at a position 5 mm from the top edge of the paper, and the area below these solid images is printed with a toner loading amount of 0.20 mg / cm. 2 The density difference caused by a 15 mm x 15 mm solid image in the halftone portion of the image was visually judged. (Evaluation Criteria) A: No difference in shading is observed B: Very slight difference in shading is observed C: Slight difference in shading is observed D: The difference in shading is clearly visible

[0109] (Evaluation 3: Evaluation of development streaks when irregular toner is increased) A commercially available color laser printer, HP Laserjet Enterprise Color M553dn, was modified to a process speed of 270 mm / s. The toner was removed from the black toner cartridge and refilled with 1:80 g of toner. This cartridge was installed in the black station, and dummy cartridges were installed in the other stations, and the printer was left in an environment of 15.0°C / 10% RH for 3 days.

[0110] The printer was equipped with XEROX4200 paper (75 g / m 2 ) was set and 5,000 sheets of a character pattern image with a print rate of 2% were printed at 15.0°C / 10% RH. At this time, the number of times the toner was rubbed was increased by printing 2 sheets per job in a mode where the machine was stopped between jobs before the next job began. After printing 5,000 sheets, toner 1:80g was further replenished and an additional 5,000 sheets were printed (total 10,000 sheets).

[0111] In this evaluation, the number of times the toner was rubbed was intentionally increased to increase the amount of irregularly shaped toner in the developing device, recreating the situation that may occur in a cleaner-less system. After passing 10,000 sheets, the toner density was 0.40 mg / cm 2 An all-black image with a toner loading amount of 1000 was printed, and the presence or absence of streaks (development streaks) on the image was confirmed. After that, images with a print rate of 2% were printed continuously, and an all-black image was printed every 1000 sheets printed, and the presence or absence of development streaks was confirmed. (Evaluation Criteria) A: No development streaks after 14,000 sheets output B: Over 13,000 sheets, under 14,000 sheets, development streaks occur C: Development streaks occur at 11,000 or more sheets and 13,000 or less sheets D: Development streaks occur at less than 11,000 sheets

[0112] <Examples 2 to 18 and Comparative Examples 1 to 6> Image output tests and evaluations were carried out in the same manner as in Example 1, except that the toner was changed as shown in Table 4. The results of the evaluations are shown in Table 4.

[0113] [Table 4]

[0114] The present disclosure relates to the following configurations. (Configuration 1) A toner comprising toner particles, The toner particles are toner base particles containing a binder resin; an organosilicon polymer composite present on the surface of the toner base particle; The organosilicon polymer composite comprises: (i) condensation products of organosilicon compounds, and (ii) a metal compound containing at least one metal atom selected from the group consisting of aluminum, zirconium, and titanium; Contains ME is a ratio of the number of the metal atoms to the sum of the numbers of carbon atoms, oxygen atoms, silicon atoms, and the metal atoms, which is obtained by X-ray photoelectron spectroscopy of the toner, The cross section of the toner observed with a scanning transmission electron microscope was analyzed with an energy dispersive X-ray spectrometer. In the EDS mapping image of the constituent elements of the cross section of the toner obtained by analyzing the toner, a ratio of the number of the metal atoms to the total number of the silicon atoms and the metal atoms in a region outside the contour of the toner base particle is defined as MX, In the EDS mapping image, domains of the metal compound are present, and when the domain diameter is 10 nm or more, the number average diameter of the domains of the metal compound is defined as MN, The ME is 1.5 x 10 -2 is as follows: The MX is 1.00 x 10 -2 Above 1.00 x 10 -1 is as follows: The MN is 15 nm or more and 80 nm or less. A toner characterized by: (Configuration 2) 2. The toner according to claim 1, wherein MN is 20 nm or more and 50 nm or less. (Configuration 3) The ME is 1.0×10 -2 is as follows: The MX is 2.00 x 10 -2 Above 8.00 x 10 -2 Below is the 3. The toner according to configuration 1 or 2. (Configuration 4) 4. The toner according to any one of configurations 1 to 3, wherein the coverage of the toner base particles with the organosilicon polymer composite is 35 area % or more and 70 area % or less. (Configuration 5) 5. The toner according to any one of configurations 1 to 4, wherein the condensate of the organosilicon compound is an organosilicon polymer having a structure represented by the following formula (I): R-SiO 3 / 2 (I) (In formula (I), R represents an alkyl group, an alkenyl group, an acyl group, an aryl group, or a methacryloxyalkyl group.) (Configuration 6) 6. The toner according to any one of configurations 1 to 5, wherein the metal atom is titanium. (Configuration 7) 7. The toner according to any one of configurations 1 to 6, wherein the metal compound is at least one metal compound selected from the group consisting of titanium dioxide and a reaction product of titanium and a polyvalent acid. (Configuration 8) The toner according to any one of configurations 1 to 7, wherein the metal compound is titanium dioxide.

Claims

1. A toner comprising toner particles, The toner particles are toner base particles containing a binder resin; an organosilicon polymer composite present on the surface of the toner base particle; The organosilicon polymer composite comprises: (i) condensation products of organosilicon compounds, and (ii) A metal compound containing at least one metal atom selected from the group consisting of aluminum, zirconium, and titanium. Contains ME is a ratio of the number of the metal atoms to the sum of the numbers of carbon atoms, oxygen atoms, silicon atoms, and the metal atoms, which is obtained by X-ray photoelectron spectroscopy of the toner, In an EDS mapping image of constituent elements of a cross section of the toner, which is obtained by analyzing the cross section of the toner observed with a scanning transmission electron microscope with an energy dispersive X-ray spectrometer, a ratio of the number of the metal atoms to the total number of the silicon atoms and the metal atoms in a region outside the contour of the toner base particle is defined as MX, In the EDS mapping image, domains of the metal compound are present, and when the domain diameter is 10 nm or more, the number average diameter of the domains of the metal compound is defined as M The ME is 1.5 × 10 -2 is as follows: The MX is 1.00×10 -2 Above 1.00 x 10 -1 is as follows: The M is 15 nm or more and 80 nm or less. A toner characterized by:

2. 2. The toner according to claim 1, wherein the M N is 20 nm or more and 50 nm or less.

3. The ME is 1.0×10 -2 is as follows: The MX is 2.00×10 -2 Above 8.00 x 10 -2 Below is the The toner according to claim 1 .

4. 2. The toner according to claim 1, wherein the coverage of said toner base particles with said organosilicon polymer composite is from 35 area % to 70 area %.

5. 2. The toner according to claim 1, wherein the condensation product of the organosilicon compound is an organosilicon polymer having a structure represented by the following formula (I): R-SiO 3/2 ・・・(@) (In formula (I), R represents an alkyl group, an alkenyl group, an acyl group, an aryl group, or a methacryloxyalkyl group.)

6. The toner of claim 1 , wherein the metal atom is titanium.

7. 2. The toner according to claim 1, wherein the metal compound is at least one metal compound selected from the group consisting of titanium dioxide and a reaction product of titanium with a polyvalent acid.

8. The toner according to any one of claims 1 to 7, wherein the metal compound is titanium dioxide.

Citation Information

Patent Citations

  • toner

    JP2021021789A

  • Toner

    JP2021021790A